Perspektywy rozwoju produkcji żywca drobiowego w Polsce w warunkach rozszerzonej Unii Europejskiej - Banaś, Katarzyna (Perspectives of Production Development of Poultry Livestock in Poland in Conditions of the Extended European Union, 2005)
The production of poultry livestock in the European Union in years 1990-2003 increased about 2,7% yearly, but in Poland about 8,4 %. Poland is in the middle scale of poultry production in comparison with the other producers in EU but is a leader among the new countries of EU.The consumption of poultry meat in Poland per capita varied from 7,6 in year 1990 to 20,0 kg in year 2003, what means increase of about 0,9 kg yearly. In the European Union the consumption of poultry increased from 18,5 kg per capita in year 1990 to 23,0 kg in year 2003, that is on average about 0,38 kg per capita yearly.The export of poultry products from Poland to EU markets shows an increased tendency. It is estimated that the production of poultry in the EU as well as in Poland will have an increasing trend.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 25-29